The Effect of Inflation and Rupiah Exchange Rate on Stock Prices with Dividends as Moderators - Masno Marjohan (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
Objectives: The choice to pay dividends is a strategic one for every business. It's the foundation on which stock market investments are made. Dividends paid out by a firm are more highly valued by shareholders than capital profits. Due to the inherent risk associated with investing, investors would rather receive compensation in the now than in the future. The company's future success may be seen in its consistent dividend payments. The goal of this research was to examine the moderating role of dividends in a market vulnerable to inflation and the rupiah exchange rate. The focus is on dividend-paying firms trading on the IDX between 2013 and 2021.Methodology: The associative quantitative approach used here relies on previously collected data. The purposive sampling method was used in the sampling process. This study used 153 samples over 9 time periods, following the criteria. Both single- and multi-linear regression are used in the study.Finding: The findings in the study are inflation and rupiah exchange rates on stock prices have a negative effect and simultaneously affect stock prices while dividends per share can moderate the connection between inflation and stock prices.Conclusion: Both inflation and the rupiah exchange rate have been shown to have a negative effect on stock prices. Inflation has been shown to have a negative influence on stock prices while the rupiah exchange rate also has this effect. According to the findings of this journal, a combined effect of inflation and the value of the rupiah against other currencies may be seen in stock market prices. Furthermore, it has been shown that this effect can occur. The MRA research also shows that dividends per share have a moderating influence on the connection between inflation and stock prices, as well as the correlation between the rupiah exchange rate and stock prices.